ANTI-FRAUD FIGHT – ATTRIBUTE OF THE ACT OF CONTROL - Mihaela Iuliana DUMITRU; Diana Elena BRÎNZĂ (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2022)
The paper aims to present the control activity carried out by the economic entities, regardless of their specificity and the main objectives pursued within it. On the other hand, emphasis is placed on the anti-fraud fight that is being carried out as a result of the practical applicability of the actual control actions. The research aimed at highlighting both the basic objectives and the correlation that is established for the anti-fraud fight carried out by different institutions, both at national and European Union level.